Industrialisasi dan Dampak Sosial di Regentschap Pemalang Masa Kolonial Belanda - Utomo, Ilham Nur; Wijayanti, Dwi (Jambura History and Culture Journal, 2025)
This research examined the dynamics of industrialization and its social impact on the inhabitants of the Regentschap Pemalang during the Dutch colonial period. Historical studies of industry still tend to focus on urban areas as the locus of research due to their role as industrial centers. However, industrialization also occurred in hinterland areas, including Regentschap Pemalang, which has so far received little scholarly attention. The method used in this research was the historical method. The findings showed that the Agrarian Law of 1870 and the Ethical Policy encouraged industrialization in the Dutch East Indies, reaching even rural or hinterland areas. Industrialization in Regentschap Pemalang, a hinterland region, is evidenced by the establishment of factories in rural areas located along the coast and in the highlands on the northern slopes of Mount Slamet. The development of industrialization had a broad impact on the lives of the people of Regentschap Pemalang, including increasingly intensive interactions between the indigenous population and Europeans, the formation of a capitalistic social structure, and the emergence of political awareness and a sense of nationalism among laborers.